Penerapan Model Addie Dalam Pengembangan Media Pembelajaran Interaktif Menggunakan Lectora Inspire Pada Program Studi Pendidikan Agama Hindu - Ni Rai Vivien Pitriani; I Gusti Ayu Desy Wahyuni; I Ketut Pasek Gunawan (Jayapangus Press, 2021)
This study aims to determine the Development of Interactive Learning Media Using Lectora Inspire in the Hindu Religious Education Study Program; determine the feasibility of this learning media based on the assessment of material experts, media experts and learning practitioners; knowing the student's assessment of this learning media. This type of research and development uses the ADDIE development model. At the Development stage, the learning media using Lectora Inspire which was assessed for feasibility by 1 material expert, 1 media expert and 1 learning practitioner, all of them from STAHN MPU Kuturan lecturers. The implementation phase includes two stages, namely small group trials and field trials. The results showed that the Learning Media Using Lectora Inspire was developed through five stages, namely Analysis, Design, Development, Implementation and Evaluation; The feasibility level of this learning media based on the assessment of material experts obtained an average of 4.53 which was included in the very feasible category, media experts obtained an average of 4.48 which was included in the very feasible category, and learning practitioners obtained an average of 4.60 which included in the very decent category; Student assessment, obtained an average overall score of 4.24 which is included in the very decent category. Based on the results of the study, the developed learning media is very suitable to be used as a learning medium in the Hindu religious education study program.